The effect of sulfate ion on the hydrogen adsorption over Pt/sulfate-ZrO2 catalyst - Triwahyono, Sugeng; Abdul Jalil, Aishah; Shamsuddin, Mustaffa; Hamdan, Halimaton (2005)

(untitled)
The influence of sulfate ion on the hydrogen adsorption over Pt/sulfate-ZrO2, has been studied. Pt/sulfate-ZrO2 samples were prepared by impregnation of Zr(OH)4 with 0.5N, 1.0N, 2.0N and 4.0N of sulfate ion and calcined at 873 K, followed by addition of 0.5wt% Pt. XRD, nitrogen physisorption and ammonia TPD have been used to monitor the physical structure of catalyst. Adsorption of hydrogen was carried out at 523 K for 8 h. The increase of sulfate ion up to 4.0 N increased the hydrogen uptake markedly. The presence of sulfate ion on catalysts exerts a promotive effect on the hydrogen uptake rate due to the development of medium and strong acid sites.